2012
DOI: 10.1103/physreve.86.016411
|View full text |Cite
|
Sign up to set email alerts
|

Flow shear stabilization of rotating plasmas due to the Coriolis effect

Abstract: A radially decreasing toroidal rotation frequency can have a stabilizing effect on nonaxisymmetric magnetohydrodynamic (MHD) instabilities. We show that this is a consequence of the Coriolis effect that induces a restoring pressure gradient force when plasma is perturbed radially. In a rotating cylindrical plasma, this Coriolis-pressure effect is canceled by the centrifugal effect responsible for the magnetorotational instability. In a magnetically confined toroidal plasma, a large aspect ratio expansion shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…, and this for all poloidal-toroidal mode number pairs. At the same time, Haverkort & de Blank (2012) clearly showed that in such 2D equilibrium settings as valid for accretion tori, a radially decreasing toroidal rotation frequency can be stabilizing for nonaxisymmetric MHD modes, by a Coriolis pressure effect. This finding is relevant both for accretion disks and for rotating, toroidally confined laboratory plasmas (which are known to feature transport barriers).…”
Section: Cylindrical Versus Toroidal Analysismentioning
confidence: 91%
“…, and this for all poloidal-toroidal mode number pairs. At the same time, Haverkort & de Blank (2012) clearly showed that in such 2D equilibrium settings as valid for accretion tori, a radially decreasing toroidal rotation frequency can be stabilizing for nonaxisymmetric MHD modes, by a Coriolis pressure effect. This finding is relevant both for accretion disks and for rotating, toroidally confined laboratory plasmas (which are known to feature transport barriers).…”
Section: Cylindrical Versus Toroidal Analysismentioning
confidence: 91%
“…The approach presented in [7] has been extensively employed for the study of highly localised (Suydam-like) modes in cylindrical and toroidal ideal plasmas [8][9][10]. Various stability criteria have been derived with both poloidal and toroidal rotation [8][9][10]. Global m=1 modes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The same is true for the TSAC modes, since in the strong field limit β 1 of magnetically dominated thick accretion tori, this continuum instability switches on whenever the squared poloidal Alfvén Mach number exceeds a value of about 1 2 γβ, and this for all poloidal-toroidal mode numbers pairs. At the same time, Haverkort & de Blank (2012) clearly showed that in such 2D equilibrium settings as valid for accretion tori, a radially decreasing toroidal rotation frequency can act stabilizing for non-axisymmetric MHD modes, by a Coriolis-pressure effect. This finding is relevant for both accretion disks and for rotating, toroidally confined, laboratory plasmas (which are known to feature transport barriers).…”
Section: Cylindrical Versus Toroidal Analysismentioning
confidence: 93%